Language Analyses of Multicultural Text Discussions: How Preservice Teachers Reflect on Their Own Talk About Multilingual Texts - Lindsey W. Rowe; Katie McGee (Education Sciences)
We present data from a qualitative study examining how one class of preservice teachers (PSTs; n = 34) engaged in book club discussions about young adult literature featuring multilingual text and protagonists. Data focus on audio recordings and written reflection notes from a book club meeting where PSTs were asked to analyze transcripts of their previous book club conversations to explore their stances related to multilingualism. We ask the following questions: (1) What moments of their own previous talk during book club discussions about multilingual texts did PSTs select to analyze, and what reasons did they state for selecting those moments? (2) How did PSTs reflect on these moments during group discussion? and (3) What larger ideologies or discourses were manifested in these reflective discussions? We used descriptive coding to identify the topics of their selected events and rationales for selection, as well as tools of microethnographic and critical discourse analysis to consider how PSTs discussed and reflected on their own and others’ stances and how these conversations pointed to broader ideologies about multilingualism and the experiences of multilingual students.